Genome-Wide Characterization and Analysis of bHLH Transcription Factors Related to Anthocyanin Biosynthesis in Fig (Ficus carica L.) - Song, Miaoyu; Wang, Haomiao; Wang, Zhe; Huang, Hantang; Chen, Shangwu; Ma, Huiqin (Frontiers in Plant Science, 2021)
The basic helix–loop–helix (bHLH) transcription factor family is the second largest transcription factor family in plants, and participates in various plant growth and development processes. A total of 118 bHLH genes were identified from fig (Ficus carica L.) through a whole-genome database search. Phylogenetic analysis with Arabidopsis homologs divided them into 25 subfamilies. Most of the bHLHs in each subfamily shared similar gene structure and conserved motifs. Seventy-two bHLHs were found expressed at FPKM > 10 in fig fruit; among them, 15 bHLHs from 8 subfamilies had FPKM > 100 in at least one sample. bHLH subfamilies had different expression patterns in the female flower tissue and peel during fig fruit development. Comparing green and purple peel mutants, 13 bHLH genes had significantly different (≥2-fold) expression. Light deprivation resulted in 68 significantly upregulated and 22 downregulated bHLH genes in the fruit peel. Sixteen bHLH genes in subfamily III were selected by three sets of transcriptomic data as candidate genes related to anthocyanin synthesis. Interaction network prediction and yeast two-hybrid screening verified the interaction between FcbHLH42 and anthocyanin synthesis-related genes. Transient expression of FcbHLH42 in tobacco led to apparent anthocyanin accumulation. Our results confirm the first fig bHLH gene involved in fruit color development, laying the foundation for an in-depth functional study of other FcbHLH genes in fig fruit quality formation, and contributing to our understanding of the evolution of bHLH genes in other horticulturally important Ficus species.